Diagnosis and management of cystic calculi in a pug - Alok, Alok kumar Chaudhary; Anuradha Nema; Shubhangi , Dr.Shubhangi Choudhary; Nisha, Dr.Nisha Chaudhary; Mukesh , Mukesh shrivastva (Indian Journal of Veterinary Medicine, 2024)
Five-year-old male pug dog with a month-long history of dribbling of urine, anorexia, dehydration,and abdominal pain was comprehensively examined. Radiography and abdominal ultrasonography, identifiedcondition as urinary bladder calculi. Urine analysis suggested urolith type and bacterial infection involvement. Alarge struvite calculus was removed from the bladder through cystotomy. The dog was placed on a modified dietand the dog had uneventful recovery with no recurrence in 3 months period.